I'm New…Again: Reconceptualizing the Socialization Process Through Rotational Programs. Issue 2 (14th March 2016) - Dailey, Stephanie L.
Abstract : Communication scholars have studied how organizations socialize new employees in breadth, but we know less about how employees adapt to multiple roles rather than just one position. With the rise of rotational programs, which introduce newcomers to several different jobs within a brief time, socialization theory should be expanded. This study focused on people's experiences in rotational programs to provide a more accurate picture of this complex socialization process. Longitudinal, qualitative data from employees during their first and second job rotation revealed that such employees' socialization differs from traditional employees' experiences. The results suggested a Model of Rotational Socialization that more accurately portrays the socialization process by accounting for the contrast between role and organizational socialization.